ADAPTATION IN ABAQUS OF THE ITERATED-ANALYTICAL MULTILAYER USER FINITE ELEMENT - Гондлях, Александр Владимирович (Eastern-European Journal of Enterprise Technologies, 2012)
There are developed and numerically implemented in ABAQUS environment based on the iterative- analytical theory relations the 8-node multilayered finite user`s element (USER_IAT_3D) for investigate the processes of nonlinear deformation and failure of spatial multi-layer systems.